INCONFORMIDADE URBANÍSTICA AMBIENTAL DO LOTEAMENTO LRCB EM CRAVINHOS (SP) - Vieira, Elias Antonio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704369 This article discusses the procedures usually employed for aproval documentationdivision of land in Cravinhos (SP), Brasil demonstrating a failure analysis project. The method usedconsisted of a literature review and analysis of documentation submitted for approval by theowners of the project area. The objective of this work is to support those interested inunderstanding an conducting the process of approval of subdivision of land for building houses inthe State of São Paulo, Brasil, specifically in Cravinhos. The results of the case study lead toconclude that the owner of the area and its advisers has difficulty in presenting appropriatedocumentation to the norms.Keywords: Land division. Technical and legal documentation. Norms for allotments of land.